2023
DOI: 10.3389/fendo.2023.1082504
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of association between visceral adiposity index and serum anti-aging protein Klotho in adults

Abstract: BackgroundThe visceral adiposity index (VAI) is regarded as a reliable indicator to assess body fat distribution and dysfunction. Klotho protein is a hormone with anti-aging biological functions. However, the relationship between them has not been researched.ObjectsThis study aimed to evaluate the association between VAI and serum anti-aging protein klotho in American adults.MethodsA cross-sectional study of participants was conducted based on the National Health and Nutrition Examination Surveys (NHANES) 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…In a very elegant study, Cui et al 4 analyzed the association between the visceral adiposity index and serum levels of the anti-aging protein Klotho protein, using (United States) National Health and Nutrition Examination Survey data. The authors found that, among adults in the United States, there was a non-linear association, as well as a dose–response relationship, between serum Klotho levels and the visceral adiposity index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very elegant study, Cui et al 4 analyzed the association between the visceral adiposity index and serum levels of the anti-aging protein Klotho protein, using (United States) National Health and Nutrition Examination Survey data. The authors found that, among adults in the United States, there was a non-linear association, as well as a dose–response relationship, between serum Klotho levels and the visceral adiposity index.…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of reactive oxidative species (ROS) and oxidative stress in adipose tissue can have various pathological manifestations 3 . It has also been demonstrated that an increase in visceral adiposity is associated with a decrease in serum Klotho protein levels; therefore, obesity induces a state of Klotho deficiency 4 . Obesity has been associated with acute kidney injury (AKI) in intensive care unit patients and in patients recovering from surgery 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Disease like insulin resistance and metabolic-associated fatty liver disease are thought to be significantly increased by high VAT mass [ 31 , 32 ]. The visceral adiposity index, an index for the evaluation of VAT, was found to be associated with aging in a study of 6,252 adults in the USA [ 33 ]. However, QCT is now thought to be a superior method for the assessment of VAT [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a very elegant study, Cui et al (4) analyzed the association between the visceral adiposity index and serum levels of the anti-aging protein Klotho protein, using (United States) National Health and Nutrition Examination Survey data. The authors found that, among adults in the United States, there was a nonlinear association, as well as a dose-response relationship, between serum Klotho levels and the visceral adiposity index.…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of reactive oxidative species (ROS) and oxidative stress in adipose tissue can have various pathological manifestations (3). It has also been demonstrated that an increase in visceral adiposity is associated with a decrease in serum Klotho protein levels; therefore, obesity induces a state of Klotho de ciency (4).…”
Section: Introductionmentioning
confidence: 99%